The Transformation of Islamic Intellectual Traditions in Palembang: From the Sultanate to the Colonial Era - Nor Huda Ali; Otoman Otoman (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This article explores the socio-intellectual history of Islam in Palembang, spanning from the Sultanate era to the colonial period. Employing a qualitative historical approach and library research, the study examines the evolution of Islamic scholarly networks, the pivotal role of local ulama, and the influence of Dutch colonial policies on religious education. Primary sources include manuscripts authored by Sheikh Abdussamad al-Palimbani, royal Sultanate documents, and Dutch colonial archives. Data were analyzed thematically using a historical-hermeneutic framework and source criticism to ensure textual authenticity and contextual accuracy. The findings demonstrate that Palembang functioned as a major intellectual hub in Sumatra, shaped by the dynamic interplay between local Islamic authority, transregional ulama networks, and the pressures of colonial administration. This study contributes to the historiography of Malay-Islamic scholarship by highlighting the adaptive resilience of religious intellectual traditions amid shifting political regimes.